THE RELEVANCE OF THE ADVERTISING SLOGAN AND THE SPECIFICITY OF ITS TRANSLATION - Е.А. Ахaпов; А.С. Дaировa (Journal of Oriental Studies, 2019)
This article is devoted to the study of features of translation of advertising slogans on the example of Japanese mass media. In this paper, we consider such issues as: the characteristics of Japanese adver- tising, in particular, the specificity of its language. Moreover, the most frequently used techniques for translating slogans from Japanese into Russian have been identified. Key words: slogan, advertising, translation, transformation, equivalence and adequacy of translation.